Economic Significance of Two-By-Two Method of Evangelism (Luke 10: 1-2) in the Anglican Diocese of Ughelli (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Evangelism is a core mandate of the Church as it is a necessity for soul-winning and salvation. The Ugheli Diocese of the Anglian Church has been carrying out this mandate over the years. However, the method usually adopted, which is the open-air crusade, is capital-intensive; yet, the method does not allow personal evangelical contact with targeted people. This is counterproductive. This paper explores the economic significance of the two-by-two model of evangelism, as instructed in Luke 10:1–2, in the context of the Anglican Diocese of Ughelli. The study is qualitative, adopting historical, descriptive survey, and analytical methods, with a target population comprising clergy, evangelists, and other community members involved in diocesan outreach programmes. Data collection involved oral interviews and personal observation methods, and analysis entailed the use of descriptive statistics and thematic interpretation. Results indicate that the effectiveness of evangelism is boosted by the two-by-two model through enhancing personal contact, collaboration, and relational engagement. More so, the method is cost-effective, as not much funding is used for evangelism. The study concludes that the biblical method of two-by-two is more impactful and cost-effective. The paper, therefore, advocates that churches, particularly those in rural areas, should adopt the two-by-two approach to evangelism to avoid spending too much, thereby placing heavy financial burdens on members.